Activation of Bentonite and Talc by Acetic Acid as a Carbonation Feedstock for Mineral Storage of CO2 - Ptáček, Petr; Nosková, Magdaléna; Šoukal, František; Opravil, Tomáš; Havlica, Jaromír; Brandštetr, Jiří (IntechOpen, 2012)
None